Murder at the Royal Botanic Gardens - Penrose, Andrea (Penrose, Andrea. Wrexford & Sloane historical mystery., 2021)
"One advantage of being caught up in a whirl of dress fittings and decisions about flower arrangements and breakfast menus is that Charlotte Sloane has little time for any pre-wedding qualms. Her love for Wrexford isn't in question. But will being a wife--and a Countess--make it difficult for her to maintain her independence--not to mention, her secret identity as famed satirical artist A.J. Quill? Despite those concerns, there are soon even more urgent matters to attend to during Charlotte and Wrexford's first public outing as an engaged couple. At a symposium at the Royal Botanic Gardens, a visiting botanist suffers a fatal collapse. The traces of white powder near his mouth reveal the dark truth--he was murdered. Drawn into the investigation, Charlotte and the Earl learn of the victim's involvement in a momentous medical discovery. With fame and immense fortune at stake, there's no shortage of suspects, including some whose ruthlessness is already known. But neither Charlotte nor her husband-to-be can realize how close the danger is about to get--or to what lengths this villain is prepared to go . . ." --Amazon.com.